Social determinants of health rather than race impact health-related quality of life in 10-year-old children born extremely preterm - Call, Catherine; Oran, Ali; O’Shea, T. Michael; Jensen, Elizabeth T.; Frazier, Jean A.; Vaidya, Ruben; Shenberger, Jeffrey; Gogcu, Semsa; Msall, Michael E.; Kim, Sohye; Jalnapurkar, Isha; Fry, Rebecca C.; et al. (Frontiers in Pediatrics, 2024)
Background Reducing healthcare disparities among children is extremely important given the potential impact of these disparities on long-term health-related quality of life (HRQL). Race and parental socioeconomic status (SES) are associated with child HRQL, but these associations have not been studied in infants born extremely preterm (EP), a population at increased risk for physical, cognitive, and psychosocial impairments. Achieving health equity for infants born EP across their life course requires identifying the impact of racism and SES on HRQL. Objective We aimed to evaluate the association between self-reported maternal race, SES factors, and HRQL among 10-year-old children born EP. Design/methods Participants were identified from an ongoing multicenter prospective longitudinal study of Extremely Low Gestational Age Newborns (ELGAN Study), born between 2002 and 2004, and evaluated at 10 years of age using the Pediatric quality of life (QoL) Inventory completed by their parent or guardian, assessing physical, emotional, social, school, and total (composite) QoL domains. Multivariable regression models were used to evaluate the relationship between QoL scores and self-identified maternal race, adjusting for SES factors (education level, marital status, and public insurance). Results Of 1,198 study participants who were alive at 10 years of age, 863 (72.0%) were evaluated at 10 years of age. Differences in mean 10-year QoL scores across racial groups were observed and were significant on univariate analysis. However, these associations attenuated when adjusted for the marital status, public insurance status, and education status of mothers. A comparison of children with English as the primary language spoken at home vs. any other language revealed a significant difference only in school QoL, in which non-English language was associated with more favorable school QoL scores. Conclusions Among 10-year-old children born EP, differences in parent-reported QoL were associated with maternal SES factors but not with race. Our results suggest that interventions designed to improve the SES of mothers may enhance the QoL of children born EP. Furthermore, these results underscore that race is a social construct, rather than a biological variable, as we work toward greater equity in care provision.